2007
DOI: 10.1159/000101923
|View full text |Cite
|
Sign up to set email alerts
|

Intraobserver Repeatability of Automated versus Adjusted Optical Coherence Tomography Measurements in Patients with Neovascular Age-Related Macular Degeneration

Abstract: Aim: To assess the intraobserver repeatability of automated versusadjusted optical coherence tomography (OCT) measurements in patients with neovascular age-related macular degeneration (NVAMD). Methods: Ten eyes with NVAMD from 10 consecutive patients underwent two OCT measurements within 5 days by a single operator. Automated and adjusted central 1-mm foveal thickness and automated and adjusted total macular volume were measured in each study eye. The term ‘adjusted’ refers to manually corrected values, in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The software version 3.0 of Cirrus OCT contains a built-in module to manually correct algorithm line failures. Although software options for the correction of Stratus OCT algorithm failures 19,20 are available, they are not built in. The data have to be exported, and they are not supported by the manufacturer of the Stratus OCT (Carl Zeiss Meditec, Inc.).…”
Section: Discussionmentioning
confidence: 99%
“…The software version 3.0 of Cirrus OCT contains a built-in module to manually correct algorithm line failures. Although software options for the correction of Stratus OCT algorithm failures 19,20 are available, they are not built in. The data have to be exported, and they are not supported by the manufacturer of the Stratus OCT (Carl Zeiss Meditec, Inc.).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we used automated CFPT and macular volume measurements obtained directly from OCT software rather than manually measuring these parameters from OCT images. Manual measurement of CFPT can allow the trained reader to eliminate software error in determining the location of topographic features such as the level of the retinal pigment epithelium or inner limiting membrane, but additional errors are introduced due to intraobserver and interobserver variation; additionally, a study comparing adjusted and automated measurements showed no overall difference between manually adjusted and automated macular volume measurement 23. Third, not all macular oedema is captured in the CFPT measurement; for this reason we also used automated macular volume measurements, which are accurate in the diagnosis of clinically significant macular oedema,24 for the curve fitting.…”
Section: Discussionmentioning
confidence: 99%
“…This led to the creation of OCT reading centers where independent observers review OCT scans for defined pathologies and retinal thickness measurements. Data regarding OCT retinal thickness measurement reproducibility has been published previously [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%